UM ð˜—ð˜©ð˜ºð˜ð˜ð˜°ð˜·ð˜¢ð˜µð˜¦ð˜´ (VATINAE) E UMA ð˜“ð˜ªð˜µð˜¶ð˜³ð˜¨ð˜¶ð˜´ð˜¢ (LITURGUSINAE) NOVOS DO BRASIL (MANTODEA-MANTIDAE) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UM ð˜—ð˜©ð˜ºð˜ð˜ð˜°ð˜·ð˜¢ð˜µð˜¦ð˜´ (VATINAE) E UMA ð˜“ð˜ªð˜µð˜¶ð˜³ð˜¨ð˜¶ð˜´ð˜¢ (LITURGUSINAE) NOVOS DO BRASIL (MANTODEA-MANTIDAE)